Association between Receipt of Intrapartum Magnesium Sulfate and Postpartum Hemorrhage - Miller, Emily M.S.; Sakowicz, Allie; Leger, Elise; Lange, Elizabeth; Yee, Lynn M. (American Journal of Perinatology Reports, 2021)
Objective The aim of the study is to investigate the association between intrapartum administration of magnesium sulfate in women with hypertensive disorders of pregnancy and postpartum hemorrhage.Study Design This was a retrospective cohort study of women diagnosed with a hypertensive disorder of pregnancy who delivered singleton gestations >32 weeks at a single, large volume tertiary care center between January 2006 and February 2015. Women who received intrapartum magnesium sulfate for seizure prophylaxis were compared with women who did not receive intrapartum magnesium sulfate. The primary outcome was frequency of postpartum hemorrhage. Secondary outcomes included estimated blood loss, uterine atony, and transfusion of packed red blood cells. Bivariable analyses were used to compare the frequencies of each outcome. Multivariable logistic regression models examined the independent associations of magnesium sulfate with outcomes.Results Of 2,970 women who met inclusion criteria, 1,072 (36%) received intrapartum magnesium sulfate. Women who received magnesium sulfate were more likely to be nulliparous, publicly insured, of minority race or ethnicity, earlier gestational age at delivery, and undergo labor induction. The frequency of postpartum hemorrhage was significantly higher among women who received magnesium sulfate compared with those who did not (12.4 vs. 9.3%, p = 0.008), which persisted after controlling for potential confounders. Of secondary outcomes, there was no difference in estimated blood loss between women who did and did not receive magnesium sulfate (250 mL [interquartile range 250–750] vs. 250 mL [interquartile range 250–750], p = 0.446). However, compared with women who did not receive magnesium sulfate, women who received magnesium sulfate had a greater frequency of uterine atony (8.9 vs 4.9%, p < 0.001) and transfusion of packed red blood cells (2.0 vs. 0.8%, p = 0.008). These differences persisted after controlling for potential confounders.Conclusion Intrapartum magnesium sulfate administration to women with hypertensive disorders of pregnancy is associated with increased odds of postpartum hemorrhage, uterine atony, and red blood cell transfusion.
Keywords: hypertensive disorders of pregnancy; magnesium sulfate; obstetrics; postpartum hemorrhage